Factors influencing surface water changes in the Khar-Us Lake basin, western Mongolia (Mongolian Journal of Geography and Geoecology, 2025)
This study investigates the spatiotemporal variability in the surface areas of Khar-Us, Khar, and Durgun Lakes in western Mongolia between 1992 and 2022 using Landsat imagery and climatic datasets. The Normalized Difference Water Index (NDWI) was employed to extract lake extents, and trend analyses such as the Mann–Kendall test, Sen’s Slope Estimator, and Innovative Trend Analysis Method were used to examine the influence of climate variables - precipitation and air temperature. Results show a statistically significant decline in lake surface area, particularly for Khar-Us Lake, which decreased by approximately 0.43 km² annually. Over the past 30 years, a strong climatic influence has been observed, as indicated by the Mann Kendall (MK) trend (Z = -2 to -6). Air temperature has exhibited a gradual warming MK trend (Z = 0.68), whereas precipitation has shown a declining trend (Z = -0.781). Climatic factors, including reduced precipitation and increasing temperatures, were identified as the dominant drivers. While surface changes in Khar and Durgun Lakes between 2006 and 2010 appear temporally aligned with the operational period of the Durgun Hydropower Plant (HPP), the current study does not include hydrological or operational data to quantitatively confirm causation. Hence, the potential influence of anthropogenic factors is discussed as a hypothesis requiring further research. These findings contribute to understanding the impacts of climatic variability on lake ecosystems in semi-arid regions.